Research Note: Bone ash from immature broilers correlates to bone mineral content calculated from quantitative computed tomography scans - Pritchard, Abby (Poult Sci, 2020)
Owing to selection for rapid growth and heavy muscle, bone deformities and injuries in broiler chickens are common and present a welfare concern. Recently, clinical quantitative computed tomography scans (QCTs) have been used for laying hens with significant, strong correlations between QCT-generated bone mineral content (BMC), bone ash, and analytical calcium. The objectives of this study were to determine if QCT-generated bone mineral density of tibias and femurs correlated to fat-free ash and if analytical Ca could be correlated to bone ash and digitally calculated density in immature broilers. Male broilers (Ross 708, n = 125) were raised from day 1 after hatching, and at 42 D, right leg quarters were collected from 50 randomly selected birds and frozen at −20°C until analysis. Leg quarters were scanned with muscle and feathers intact and arranged in rows on plexiglass, and each QCT included a solid Ca hydroxyapatite phantom. Tibias and femurs were removed from leg quarters after autoclaving, ashed, and weighed. Pearson's correlation analysis was conducted to understand the association between analytical bone ash and QCT BMC while paired t tests determined the amount of difference between QCT BMC and ash. Ash weight was strongly correlated to QCT BMC in both the femur (R = 0.86, P < 0.001) and the tibia (R = 0.91, P < 0.001). The average difference between the amount of actual ash weighed and BMC calculated from the QCT was 0.03 ± 0.22 g (P = 0.3) for the femur and 0.04 ± 0.22 g (P = 0.2) for the tibia. This study confirms that this technique can supply invaluable skeletal health information without sacrificing birds.